Effect of Nano-CaCO3 on the Mechanical Properties and Durability of Concrete Incorporating Fly Ash - Yanqun Sun; Peng Zhang; Weina Guo; Jiuwen Bao; Chengping Qu (Advances in Materials Science and Engineering)
Concrete mixtures consisting of nanomaterials and fly ash have been shown to be effective for improving the performance of concrete. This study investigates the combined effects of nano-CaCO3 and fly ash on the mechanical properties and durability of concrete; the mix proportion is optimized through orthogonal experiments. In the first phase, nine concrete mixtures were prepared with three water-to-binder ratios (0.4, 0.5, and 0.6), three fly ash contents (15%, 20%, and 25% replacement of the cement weight), and three nano-CaCO3 contents (1%, 2%, and 3% replacement of the cement weight). Based on the orthogonal analysis, the optimal concrete mix proportion was determined as a water-to-binder ratio of 0.4, 20% fly ash, and 1% nano-CaCO3. In the second phase, further investigations were carried out to examine the superiority of the optimal concrete and evaluate the synergistic effect of nano-CaCO3 and fly ash. The results showed that nano-CaCO3 contributed to increasing the compressive strength of fly ash concrete at the early ages, but its effect was quite limited at later ages. Furthermore, the scanning electron microscopy analysis revealed that the seeding effect, filling effect, and pozzolanic effect were the primary mechanisms for the improvement of concrete performance.